A Reproducible Mouse Model of Moderate CKD With Early Manifestations of Osteoblastic Transition of Cardiovascular System - Machado, Sarah E; Spangler, Daryll; Black, Laurence M.; Traylor, Amie M.; Balla, József; Zarjou, Abolfazl (Frontiers in Physiology, 2022)
Chronic kidney disease (CKD) is a significant public health challenge with a substantial associated risk of mortality, morbidity, and health care expenditure. Culprits that lead to development and progression of CKD are multifaceted and heterogenous in nature. This notion underscores the need for diversification of animal models to investigate its pathophysiology, related complications, and to subsequently enable discovery of novel therapeutics. Importantly, animal models that could recapitulate complications of CKD in both genders are desperately needed. Cardiovascular disease is the most common cause of death in CKD patients that may be due in part to high prevalence of vascular calcification (VC). Using DBA/2 mice that are susceptible to development of VC, we sought to investigate the feasibility and reproducibility of a unilateral ischemia-reperfusion model followed by contralateral nephrectomy (UIRI/Nx) to induce CKD and its related complications in female and male mice. Our results demonstrate that irrespective of gender, mice faithfully displayed complications of moderate CKD following UIRI/Nx as evidenced by significant rise in serum creatinine, albuminuria, higher degree of collagen deposition, elevated expression of classic fibrotic markers, higher circulating levels of FGF-23, PTH and hepcidin. Moreover, we corroborate the osteoblastic transition of aortic smooth muscle cells and cardiomyocytes based on higher levels of osteoblastic markers namely, Cbfa-1, osteopontin, osteocalcin, and osterix. Our data confirms a viable, and consistent model of moderate CKD and its associated complications in both male and female mice. Furthermore, early evidence of osteoblastic transition of cardiovascular system in this model confirms its suitability for studying and implementing potential preventive and/or therapeutic approaches that are urgently needed in this field.